2002
DOI: 10.4049/jimmunol.168.9.4455
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CD8+ T Cell Memory in Response to Low, High, and Excessive Levels of Epitope

Abstract: The magnitude of a virus-specific memory CTL population can dramatically influence the outcome of secondary infections, yet little is known about the determinants of memory size. We investigated the impact of epitope levels on CTL memory generation by using a recombinant vaccinia virus system that allows for a broad range of epitope expression with the same infectious dose of virus. The size of the memory pool was examined using MHC class I/peptide tetramer staining and IFN-γ ELISPOT analysis following priming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 31 publications
5
71
1
Order By: Relevance
“…We find similar correlations between infection dose and population sizes in the CD8 + T cell compartment (Fig. 5B), as reported previously by others [22,23]. Thus, it seems unlikely that differences in antigen load requirements cause the different re-expansion characteristics of CD4 + and CD8 + Listeria-specific effector T cells.…”
Section: In Vivo Expansion Of Antigen-specific Cd4 + and Cd8 + Memorysupporting
confidence: 90%
“…We find similar correlations between infection dose and population sizes in the CD8 + T cell compartment (Fig. 5B), as reported previously by others [22,23]. Thus, it seems unlikely that differences in antigen load requirements cause the different re-expansion characteristics of CD4 + and CD8 + Listeria-specific effector T cells.…”
Section: In Vivo Expansion Of Antigen-specific Cd4 + and Cd8 + Memorysupporting
confidence: 90%
“…Thus, it was shown that at least two distinct subpopulations of CD4 + T-cells develop after resolution of experimental L. (L.) major infection, but only one requires the presence of the parasite (Wherry et al 2002, Gollob et al 2005. In humans, it is difficult to determine whether or not long life immunity is dependent on the persistence of parasite in tissues, since they are frequently exposed to new infections in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have addressed the requirements for generation of CD8 + memory cells (Hamann et al 1999, Wherry et al 2002, but little is known about the establishment of long lived CD4 + T-cells (Gollob et al 2005). Thus, it was shown that at least two distinct subpopulations of CD4 + T-cells develop after resolution of experimental L. (L.) major infection, but only one requires the presence of the parasite (Wherry et al 2002, Gollob et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…In primary infection, the amount of Ag determines the size of the murine CD8 ϩ T cell response. Subsequently, the magnitude of this CD8 ϩ T cell response sets the size of the Ag-specific T cell pool during the memory phase (35,36). Recently, it was demonstrated that the contraction phase of the primary immune response is independent of the clearance of Ag (37).…”
Section: Discussionmentioning
confidence: 99%